Pengembangan Kawasan Ekowisata Pulau Maitara Kota Tidore Kepulauan - Wiwin Prasetaji Sadik; Rahmawati Rahman; Ilham Yahya (Fakultas Teknik Universitas Bosowa, 2021)
Abstract. The purpose of this study is to formulate directions for the development of the Maitara Island Tourism area, Tidore Archipelago City as an Ecotourism area. The main problem then produces sub-problems or research questions about